Pengaruh Karyawan dan Jumlah Kantor Bank Syariah terhadap Pertumbuhan Aset Bank Syariah di Indonesia - Mahyudin; Nuhbatul Basyariah (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2019)
The aim of this study is to analyze the effect of the number of employees and the number of Islamic bank offices on the growth of total assets in Islamic banking (BUS, UUS, and SRB) in Indonesia. This type of research is quantitative research. The study uses secondary data in the form of monthly data from the number of workers, number of offices, and the number of Islamic banking assets (BUS, UUS, and SRB) from January 2014 to October 2018, sourced from Bank Indonesia Sharia Banking Statistics and the Financial Services Authority. Tested with multiple linear regression, Ordinary Least Square (OLS). The results of the study concluded that the number of workers and the number of Islamic banking offices have a positiv effect on the growth of the number of assets in Islamic banking. The coefficient of determination (R2) shows that the R Square value is 0.553. That is, the magnitude of the effect of the number of workers and the number of offices on the total growth of Islamic banking assets is 55.3%. While 45.7% is influenced by other variables.